SLAMF8 Participates in Acute Renal Transplant Rejection via TLR4 Pathway on Pro-Inflammatory Macrophages - Teng, Lisha; Shen, Lingling; Zhao, Wenjun; Wang, Cuili; Feng, Shi; Wang, Yucheng; Bi, Yan; Rong, Song; Shushakova, Nelli; Haller, Hermann; Chen, Jianghua; Jiang, Hong (Frontiers in Immunology, 2022)
Background: Acute rejection (AR) in kidney transplantation is an established risk factor that reduces the survival rate of allografts. Despite standard immunosuppression, molecules with regulatory control in the immune pathway of AR can be used as important targets for therapeutic operations to prevent rejection. Methods: We downloaded the microarray data of 15 AR patients and 37 NAR from GEO. Gene network was constructed and genes were classified into different modules using WGCNA. KEGG and Cytoscape were applied for the hub genes in the most related module to AR. Different cell types were explored by xCell online database and single-cell RNA sequencing. We also validated the SLAMF8 and TLR4 levels in Raw264.7 and human kidney tissues of TCMR. Results: A total of 1561 differentially expressed genes were filtered. WGCNA was constructed and genes were classified into 12 modules. Among them, the green module was most closely associated with AR. These genes were significantly enriched in 20 pathway terms, such as Cytokine-cytokine receptor interaction, Chemokine signaling pathway and other important regulatory processes. Intersection with GS > 0.4, MM > 0.9, the top 10 MCC values and DEGs in the green module, 6 hub genes (DOCK2, NCKAP1L, IL2RG, SLAMF8, CD180 and PTPRE) were identified. The expression levels of them were all confirmed significantly elevated in AR patients in GEO, Nephroseq and qRT-PCR. Single-cell RNA sequencing showed AR patient had a higher percentage of Native T, CD1C+_B DC, NKT, NK and monocytes in PBMCs. Xcell enrichment scores of 20 cell types were significantly different(P<0.01), mostly immune cells, such as B-cells, CD4+ Tem, CD8+ T-cells, CD8+ Tcm, Macrophages, M1and Monocytes. GSEA suggests that highly expressed 6 hub genes are correlated with allograft rejection, interferon γ response interferon α response and inflammatory response. In addition, SLAMF8 highly expressed in human kidney tissues of TCMR and in M1 Phenotype macrophages of Raw264.7 cell line WGCNA accompanied by TLR4 high expression. Conclusion: This study demonstrates six hub genes and functionally enriched pathways related to AR. SLAMF8 is involved in the M1 macrophages via TLR4 which contributed to AR process.